HUBUNGAN PROKRASTINASI AKADEMIK DAN SELF-EFFICACY DENGAN KETIDAKJUJURAN AKADEMIK DALAM PEMBELAJARAN ONLINE MAHASISWA KEDOKTERAN UNIVERSITAS PEMBANGUNAN NASIONAL "VETERAN" JAKARTA - Muhammad Faishal Hilmy (2023)
Academic dishonesty is behavior that can cause students to sacrifice their integrity and result in low professionalism in the world of work later. Dishonesty is influenced by various factors including procrastination and self-efficacy then online learning can also lead to academic dishonesty behavior. This study aims to determine the relationship between academic procrastination and self-efficacy with academic dishonesty in online learning for medical students at the University Pembangunan Nasional "V eteran" Jakarta. This research is an analytic study with a cross sectional design with proportional startifed random sampling method. The sample in this study amounted to 229 students with the research instrument using a questionnaire. Data analysis using Spearman rank correlation test and multiple linear regression. Correlation test results obtained p = 0,000, for academic procrastination with academic dishonesty, while for self-efficacy with academic dishonesty p = 0,003 simultaneously, all independent variables have a significant effect with a value of 3,4% on academic dishonesty in online learning. conclusion that academic procrastination and self- efficacy have a significant relationship with academic dishonesty in online learning. all independent variables simultaneously have a significant effect on academic dishonesty in online learning.